Perry Lowery: Cornet King - Christy Davis (Symphony in the Flint Hills, 2014)
Perry George Lowery was born on the road. The child who would earn a reputation as the “world’s greatest cornet soloist and band master” came into the world on October 11, 1869, in the midst of his family’s migration to Kansas. They were among the thousands of African Americans who arrived in Kansas during the post-Reconstruction Black Exodus.
Keywords: African-Americans; black; Civil War; post-reconstruction; exodus; migration; cornet; musical; Musician; Perry George Lowery; Topeka; Greenwood County; pioneer; freed; slaves; Emancipation; Spring Creek; Labina Stepter; William Stepter; band; Ringling Brothers; Barnum and Bailey; circus; Windjammers; Kansas Colored Volunteers